Community inclusion: ideology, market forces and technology. (April 2015) - Jackson, Robin
Abstract : This paper reflects upon the content of this special issue. First, it is noted that ideologists who single-mindedly promote a narrow form of inclusion fail to recognize they are seeking the realization of an unattainable utopian ideal. Second, the established fact that friendships are strongly based on the tendency of individuals to associate and bond with similar others means it is unrealistic to assume that all people with an intellectual disability can be fully included in the community. Third, the claim is examined that notwithstanding government policy on promoting social and community inclusion, people with intellectual disabilities have achieved little or no profile for most of the last twenty years. Fourth, it is noted that the rapid marketisation of the social care sector presents a challenge to the quality of life experienced by many people with an intellectual disability.